The decline of the independent inventor a Schumpterian story - Lamoreaux, Naomi R. 1950-; Sokoloff, Kenneth L. 1952-2007 (National Bureau of Economic Research, 2005)
"Joseph Schumpeter argued in Capitalism, Socialism and Democracy that the rise of large firms' investments in in-house R&D spelled the doom of the entrepreneurial innovator. We explore this idea by analyzing the career patterns of successive cohorts of highly productive inventors from the late nineteenth and early twentieth centuries. We find that over time highly productive inventors were increasingly likely to form long-term attachments with firms. In the Northeast, these attachments seem to have taken the form of employment positions within large firms, but in the Midwest inventors were more likely to become principals in firms bearing their names. Entrepreneurship, therefore, was by no means dead, but the increasing capital requirements--both financial and human--for effective invention and the need for inventors to establish a reputation before they could attract support made it more difficult for creative people to pursue careers as inventors. The relative numbers of highly productive inventors in the population correspondingly decreased, as did rates of patenting per capita"--National Bureau of Economic Research web site.
Keywords: Schumpeter, Joseph Alois <1883-1950>; Geschichte; Inventions -- Economic aspects -- United States; Inventors -- United States -- History; USA